STRATEGI PENGEMBANGAN AGROINDUSTRI KACANG SANGRAI UD. MERPATI DI DESA TOMBASIAN ATAS KECAMATAN KAWANGKOAN BARAT (Agroindustry Development Strategy of Roasted Beans â€œUD. Merpatiâ€ in Tombasia Village of Kawangkoan Barat District, Minahasa Regency) - Linda Mariani Lumantow; Theodora M. Katiandagho; Sherly G. Jocom (Jurusan Sosial Ekonomi Pertanian, Fakultas Pertanian Universitas Sam Ratulangi, Manado, 2021)
The purpose of this research was to formulate a strategy in developing the Roasted Bean AgroindustryÂ ofÂ â€œUD.Â Merpatiâ€Â in Tombasian Atas Village, West Kawangkoan District. The research was conducted from February to April 2021. The data used in this study were primary data and secondary data. The analysis used in this study was the SWOT analysis method. Based on the SWOT diagram analysis, the position of the Roasted Peanut Agroindustry â€œUD. Merpatiâ€ was in quadrant I, which was an aggressive strategy. The strategies needed to be carried out wereÂ maintaining the taste of the product, maximizing a good workforce, maximizing cooperative relationships, utilizing business licenses to further expand the target market, utilizing support from the government, utilizing technology, increasing promotions, increasing capital through related agencies, maintaining and improving product quality, collaborating with many peanut farmers, maximizing raw materials from â€œSejatiâ€ farmer groups, using social media to attract consumers, making product packaging more attractive, increasing stock of raw materials.